Histopathological analysis of autoimmune hepatitis with "acute" presentation: Differentiation from drug‐induced liver injury. Issue 9 (13th July 2020) - Tsutsui, Akemi; Harada, Kenichi; Tsuneyama, Koichi; Nguyen Canh, Hiep; Ando, Midori; Nakamura, Satoko; Mizobuchi, Koichi; Baba, Nobuyuki; Senoh, Tomonori; Nagano, Takuya; Shibata, Hiroshi; Aoki, Tomoko; et al.
Abstract : Aim: Presently, no standardized definition or acceptable diagnostic criteria have been established for acute presentation of autoimmune hepatitis (AP‐AIH), making it difficult to differentiate that condition from drug‐induced liver injury (DILI). This study aimed to characterize clinical and histological features for distinguishing between AP‐AIH and DILI. Methods: Clinical, biochemical, and histological characteristics of AP‐AIH and DILI in clinically well‐characterized cases were compared in a standardized manner to clarify differences. Results: In clinical evaluations, immunoglobulin G level and rate of anti‐nuclear antibody positivity were greater in AP‐AIH than DILI cases. As for diagnosis of each condition, significant ( P < 0.01) differences were found for 10 features: lobular necrosis/inflammation, cobblestone appearance of hepatocytes, plasma cell infiltration in liver parenchyma, centrilobular fibrosis, hepatic rosette formation in areas with cobblestone appearance, portal inflammation, interface hepatitis, prominent plasma cells in portal areas, bile duct injury, and hepatic rosette formation in periportal areas. The area under the curve and cut‐off values for the combination of these 10 features were 0.95 and 9 (sensitivity 86%, specificity 90%), respectively. Conclusion: Combinations of histological features were found to be helpful for differentiating AP‐AIH from DILI, but we were not able to statistically identify an individual feature as definitive.